1996
DOI: 10.1152/physiologyonline.1996.11.6.262
|View full text |Cite
|
Sign up to set email alerts
|

Intercellular Waves of Communication

Abstract: Intercellular Ca2+ waves may be propagated through multicellular systems by the diffusion, through gap junctions, of the second messenger inositol 1, 4, 5-trisphosphate (IP3). This intercellular IP3 signaling provides a mechanism by which cooperative cell activity may be coordinated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 0 publications
2
40
0
Order By: Relevance
“…Calcium oscillations may represent a general mechanism by which cells communicate via inositol 1,4,5-triphosphate through gap junctions [10]. In the present study, the ATP-induced [Ca2+]i increase in calcium oscillations was synchronized among adjacent cells in the wing cell layer.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Calcium oscillations may represent a general mechanism by which cells communicate via inositol 1,4,5-triphosphate through gap junctions [10]. In the present study, the ATP-induced [Ca2+]i increase in calcium oscillations was synchronized among adjacent cells in the wing cell layer.…”
Section: Discussionsupporting
confidence: 52%
“…Spikes in the wing cells did not affect the [Ca2+]i dynamics of the superficial cells. These findings indicate that communication was progressively restricted by a repetitive increase in [Ca2+]; [10], and that the propagation of the [Ca2+]i increase was not an infinite phenomenon.…”
Section: Resultsmentioning
confidence: 69%
“…Such signaling is now well established to occur by two distinct pathways -gap junctional and paracrine -and both may operate in a given situation (Boitano et al, 1992;Sanderson, 1996;Giaume and Venance, 1998;Homolya et al, 2000;Braet et al, 2001;Jorgensen et al, 2002;Schuster et al, 2003;Bennett et al, 2006;Henriksen et al, 2006;Scemes and Giaume, 2006). The former involves intercellular diffusion through gap junction channels of a molecular signal, usually considered to be IP3 and/or Ca.…”
Section: Junctional Channelsmentioning
confidence: 99%
“…Numerous studies have documented that perturbation of gap junctional communication in tissues known to be sites of CF manifestations is associated with the dysfunction of epithelial cells. For example, blockade of gap junctional communication alters the synchronized ciliary beating of tracheal cells and enhances the basal release of digestive enzymes by pancreatic acinar cells (23,48). The CFPAC-1/PLJ-CFTR lines are known to have retained typical features of the native cells from which they derived (24,25).…”
Section: Figurementioning
confidence: 99%
“…In keeping with this view, several studies have shown that agents that activate or inhibit CFTR activity in various epithelial cells also alter their capability for intercellular communication (17)(18)(19). Conversely, disruption of gap junctional communication has been associated with altered functions in tissues in which manifestations of CF occur (20)(21)(22)(23). However, whether epithelial cells devoid of functional CFTR exhibit abnormal intercellular communication is not known.…”
Section: Introductionmentioning
confidence: 99%